Study of the ınfluence of coordınated regulatıon on the traffıc flow parameters on ıntersectıng streets - Fuad Dashdamirov; Turan Verdiyev (Збірник наукових праць Державного університету інфраструктури та технологій: серія "Транспортні системи і технології", 2025)
The article studies the nature of changes in traffic flow parameters on the intersecting streets when using coordinated regulation to organize uninterrupted traffic on city highways. The influence of the "green wave" mode on the traffic flow parameters is analyzed. Traffic delays on intersecting streets were compared before and after the implementation of coordinated regulation. Traffic delay values at intersections were determined and analyzed in a comparative manner using the Webster and HCM 2010 methodology and simulation tests. Measurements were carried out based on real values (speed and traffic intensity on sections) taken at 7 intersections of the street network of the city of Baku. For simulation tests, a coordinated regulation model built in the PTV VISSIM program was used. Using the created micromodel, the results of the impact of the implementation of coordinated regulation on traffic delays on main and intersecting streets were tested. The total time losses on the street where the "green wave" is implemented and on intersecting streets were estimated for the options before and after the coordination of traffic light modes. Based on the values determined by all three methods, it was found that after the implementation of coordinated regulation on the main street the delay time of vehicles increases on intersecting streets. The proposed approach can help to evaluate the effectiveness of coordinated regulation in terms of time losses before its implementation on city streets.